TOUR GUIDE ATTITUDE AND TOURIST RESPONSE IN VIRTUAL TOUR: APPRAISAL ANALYSIS: SIKAP TOUR GUIDE DAN RESPON WISATAWAN DALAM VIRTUAL TOUR: ANALISIS APPRAISAL - Suroto Suroto; Anit Pranita Devi; Rasya Risyafa Putri; Adinda Maulida (Jurnal Kata, 2022)
Regardless of its importance in tourism, the use of appraisal theory in tourism research, particularly in the context of virtual tours, is relatively unexplored. This study aims to analyze the attitude of tour guides when describing tourist attractions and to find out the response of tourists. This research is a qualitative descriptive study. Data collection techniques were carried out by observation, documentation and questionnaires. Based on the appraisal analysis of the tour guides, there are two types of positive attitudes; affect (1%) and appreciation (99%). Tourists’ responses in the form of their satisfaction were measured by questionnaires based on the theory of tourist attraction and consumer satisfaction theory with the Likert model assessment technique. Tourists were given a questionnaire to find out whether they were satisfied with the virtual tour. They responded by strongly agree (28%), agree (49%) and neutral answer (22%). Those who responded disagree were only 1%. The tourist responses indicate that most tourists are satisfied with the virtual tour.